Social Issues as Contents for Language Communication in an English Classroom: A Theatre-based Study - Shriganeshan, K. (Vavuniya Campus of the University of Jaffna, 2010)
Language expression occurs whenever there is a need for communication. English Language Teaching is done in Sri Lankan schools to promote students' ability of expression in English. But the reality is that majority of them are unable to make oral and written communication fluently and effectively. Even with the new text books which do not reflect the students' social reality and do not provide the enthusiasm needed to the learner, teachers are unable to motivate students to communicate well. In this context, it is found that once students are made conscious of the social issues which are very much relevant in their day to day life they would be tempted to express their feelings about it in a conditioned atmosphere in a theatre workshop. This is a way to promote them to communicate well. This is well observed in an ethnographical study conducted with 38 students, a mixed group of classes 7, 8 and 9 from a school in Vavuniya, a northern city in Sri Lanka. Students were introduced to pictures, poems, stories in a theatre workshop which motivated them with warm-up exercises and games. The study was conducted for a period of three-weeks. The students were able to communicate well in the workshop as characters of a drama piece created by themselves and drafted out the scripts with full of ideas enacted in groups. This paper makes an attempt to analyse the scripts and show how the students' language development promoted and enriched by the contents which are based on social issues.
Keywords: Language expression; Enactment; Social reality